Avaliação do impacto ambiental na construção: comparação entre diferentes sistemas de alvenaria estrutural - Silva, Douglas Henrique da (Universidade Federal de São Carlos, 2024)
The methodologies for analyzing the performance of materials have been increasingly utilized within the construction industry. Comparing construction methods in terms of the life cycle of their constituent materials is one way to conduct these analyses. This study aims to contribute to this topic by comparing three construction systems using the results of a Life Cycle Assessment (LCA) for a building project based on each system. After reviewing the literature, indicators of potential impact regarding CO2 emissions, energy consumption, and water consumption were gathered for each component and material constituting the three construction methods. Subsequently, the quantity of materials needed for the building construction was determined according to the project specifications. With the total impact map of each component, it was possible to evaluate the key materials concerning their contribution to the overall impact resulting from the building construction using one of the three methods. The method with the highest impact was the cast-in-place concrete wall in terms of CO2 emissions, while the concrete block wall had the highest embodied energy. The ceramic block system showed the lowest overall impacts; however, when comparing only the transportation impacts of each system, it exhibited the highest values. It was also possible to identify, within each method, the material and component with the greatest potential impact concerning the analyzed parameters, as well as which method had the lowest total potential impact across each parameter.
Environmental impact assessment in construction: comparison between different structural masonry systems
Keywords: Impacto ambiental; Alvenaria estrutural; Construção; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL